POPULATION DYNAMICS AND STOCK ASSESSMENT OF THE SPIDER PRAWN, NEMATOPALAEMON TENUIPES HENDERSON ALONG THE MAHARASHTRA COAST - DESHMUKH, VINAY D. (Journal of Indian Fisheries Association, 2015)
Nematopalaemon tenuipes is an important component of non-penaeidprawn resources of the northwest coast of India. During 1979-82 periodit contributed 29.9% to the non-penaeid prawn and 5.6% to the total fishlandings of Maharashtra. The von Bertalanffy growth parameter Loo, Kand t were 77.38 mm, 1.31 and -0.02 year for the m.ales while for the 0females these parameters were respectively 87.23 mm, 1.30 and -0.01 year.The natural mortality coefficient (M) was 3.54 and 3.52 and the averagetotal mortality coefficient (Z) during the period was 9.09 and 7. 79 for themales and females respectively. With the exploitation rates of 0.61 and0.55 for the males and females during the period, the total stock of thespecies was 26,270 tonnes and the standing stock was 3,418 to:nnes. Themaximum sustainable yield (MSY) of the species under the prevailingfishing conditions was 15,744 tonnes which is close to the average yieldof 14,726 tonnes from the dol nets. Hence further increase in effort is notsuggested.